2022
DOI: 10.3390/ijms23168979
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NLRP3-Mediated Neuroinflammation in Alzheimer’s Disease Treatment

Abstract: Alzheimer’s disease (AD) is the most common cause of dementia in the general population and, to date, constitutes a major therapeutic challenge. In the pathogenesis of AD, aggregates of amyloid β (Aβ) and neurofibrillary tangles (NFTs) containing Tau-microtubule-associated protein (tau) are known to trigger a neuroinflammatory response with subsequent formation of an inflammasome. In particular, the NOD-like receptor pyrin domain-containing 3 (NLRP3) inflammasome is thought to play a crucial role in AD-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 151 publications
0
14
0
1
Order By: Relevance
“…In monocytes of AD patients, the mRNA and protein levels of NLRP3 are significantly increased ( Saresella et al, 2016 ), and NLRP1 is activated in the hippocampus of AD patients ( Španić et al, 2022 ). The abnormal Aβ and Tau induce inflammation through specific pathways involving MYD88 or NF-κB ( Yang et al, 2020 ; Barczuk et al, 2022 ), leading to the transcription of pro-IL-β and NLRP3 ( Lee J. H. et al, 2021 ; Leng and Edison, 2021 ). Increasing evidence has shown that soluble Aβ oligomers can activate the NLRP3 inflammasome in microglia ( Lučiūnaitė et al, 2020 ), while deletion or inhibition of NLRP3 in APP/PS1 in mice will reduce spatial memory loss and Aβ aggregation ( Michael et al, 2012 ; Dempsey et al, 2017 ; Feng et al, 2018 ).…”
Section: Microglia Recognize Pathogens By Pattern Recognition Receptorsmentioning
confidence: 99%
“…In monocytes of AD patients, the mRNA and protein levels of NLRP3 are significantly increased ( Saresella et al, 2016 ), and NLRP1 is activated in the hippocampus of AD patients ( Španić et al, 2022 ). The abnormal Aβ and Tau induce inflammation through specific pathways involving MYD88 or NF-κB ( Yang et al, 2020 ; Barczuk et al, 2022 ), leading to the transcription of pro-IL-β and NLRP3 ( Lee J. H. et al, 2021 ; Leng and Edison, 2021 ). Increasing evidence has shown that soluble Aβ oligomers can activate the NLRP3 inflammasome in microglia ( Lučiūnaitė et al, 2020 ), while deletion or inhibition of NLRP3 in APP/PS1 in mice will reduce spatial memory loss and Aβ aggregation ( Michael et al, 2012 ; Dempsey et al, 2017 ; Feng et al, 2018 ).…”
Section: Microglia Recognize Pathogens By Pattern Recognition Receptorsmentioning
confidence: 99%
“…In vivo studies testing specific inhibitors of NLRP3 have yielded promising results, such as a decrease of tau and Aβ aggregates and amelioration of the cognitive impairment (Barczuk et al, 2022). Small‐molecule NLRP3 inhibitors such as MCC950 have been shown to improve cognitive function and reduce Aβ accumulation (Dempsey et al, 2017; X. F. He et al, 2020).…”
Section: Effects Of Adipokines On the Brain And Cerebrovascular Syste...mentioning
confidence: 99%
“…Beyond these disorders, the role of NLRP3 and its downstream effects through IL‐1 have been implicated in nearly every organ in humans. While some are perhaps more obvious given clear associations with known inflammasome triggers such as in silicosis 167 or asbestosis, 168 others such as neurodegenerative disorders 169 and ovarian aging 153 have been linked to excess NLRP3 activation and expression (Figure 8). For these challenging disorders, inhibitors of NLRP3 have been shown to reduce inflammation in vitro and in vivo, lending new opportunities for intervention.…”
Section: Expanding Role For Nlrp3 In Human Diseasementioning
confidence: 99%